Embodying our future through collaboration: The change is in the doing. Issue 4 (8th August 2018) - Palmer, Marilyn; White, Peta; Wooltorton, Sandra
ABSTRACT: Contributors to this special edition have agreed that we want a future of ecojustice and ecological sustainability. Our article unpacks experiences of oppression within the context of middle class academic privilege, undertaking resistances and working, in relationship, learning to live more sustainably in the Year of Living Sustainably. In this writing, we argue the case for activism in the academy and collaboratively build resilience toward more sustainable ways of being. By co-writing and analyzing fictionalized stories, we demonstrate how contemporary universities contribute to the unsustainability of social and ecological systems. This article presents a love story grounded in poststructural ecofeminist epistemology using collaborative autoethnography. Rather than re-presenting a heroic masculinist narrative of transcendence and success, we describe how our loving relationships support our activism.